Network Analysis of Different Exogenous Hormones on the Regulation of Deep Sowing Tolerance in Maize Seedlings - Chen, Fenqi; Ji, Xiangzhuo; Bai, Mingxing; Zhuang, Zelong; Peng, Yunling (Frontiers in Plant Science, 2021)
The planting method of deep sowing can make the seeds make full use of water in deep soil, which is considered to be an effective way to respond to drought stress. However, deep sowing will affect the growth and development of maize (Zea mays L.) at seedling stage. To better understand the response of maize to deep sowing stress and the mechanism of exogenous hormones [Gibberellin (GA3), Brassinolide (BR), Strigolactone (SL)] alleviates the damaging effects of deep-sowing stress, the physiological and transcriptome expression profiles of seedlings of deep sowing sensitive inbred line Zi330 and the deep-tolerant inbred line Qi319 were compared under deep sowing stress and the conditions of exogenous hormones alleviates stress. The results showed that mesocotyl elongated significantly after both deep sowing stress and application of exogenous hormones, and its elongation was mainly through elongation and expansion of cell volume. Hormone assays revealed no significant changes in zeatin (ZT) content of the mesocotyl after deep sowing and exogenous hormone application. The endogenous GA3 and auxin (IAA) contents in the mesocotyl of the two inbred lines increased significantly after the addition of exogenous GA3, BR, and SL under deep sowing stress compared to deep sowing stress, while BR and SL decreased significantly. Transcriptome analysis showed that the deep seeding stress was alleviated by GA3, BR, and SLs, the differentially expressed genes (DEGs) mainly included cellulose synthase, expansin and glucanase, oxidase, lignin biosynthesis genes and so on. We also found that protein phosphatase 2C and GA receptor GID1 enhanced the ability of resist deep seeding stress in maize by participating in the abscisic acid (ABA) and the GA signaling pathway, respectively. In addition, we identified two gene modules that were significantly related to mesocotyl elongation, and identified some hub genes that were significantly related to mesocotyl elongation by WGCNA analysis. These genes were mainly involved in transcription regulation, hydrolase activity, protein binding and plasma membrane. Our results from this study may provide theoretical basis for determining the maize deep seeding tolerance and the mechanism by which exogenous hormones regulates deep seeding tolerance.